The effects of production methods on the microstructures and mechanical properties of an aluminum bronze - Kaplan, A; Yildiz, AK (Elsevier, 2003)
The purpose of this study is to investigate the mechanical properties and microstructures of an aluminum bronze subjected to some physical treatments. In particular, the solidification structure, the effects of solution treatment, tempering heat treatment and mold types on the microstructure of the aluminum bronze produced in two different molds are examined. The results showed that the heat treatments have some interesting effects on the mechanical properties, microstructures and phase transformation temperatures of the samples. It was obtained that alpha + beta(1) and alpha + beta(1)' phase transformation were formed depending on both the die casting and the heat treatments, but in contrast alpha + beta phase was formed in the sand-casting specimen. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: aluminum bronze; sand casting; die casting; heat treatment; microstructure